A baby monitoring system - Tan, Xing Hao (2019)
Sudden Infant Death (SID) is one of the leading causes of a baby death. Despite measures such as educational materials and messages about the risk of SID, and existing baby monitoring products, there are still a number of babies died of SID in the world. This project aims to improve the limitations of the existing baby monitoring products by tackling the possible causes that lead to SID. A baby monitoring system with capabilities to detect room temperature and to detect the movements and sound of a sleeping baby will be built to reduce the possible risk of SID. An Android application will be designed for the parents to monitor the room temperature, movements and sound of the sleeping baby on the smartphone. Additional features such as lullabies and night light will be implemented to soothe the sleeping baby. Lastly, this project has shown that parents will be able to monitor their baby through an Android application and have an increased knowledge of SID.